2018
DOI: 10.1038/s41598-018-26430-4
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical properties are associated with the activity and prognosis of Angioid Streaks

Abstract: The aim of the current study is to investigate corneal biomechanical properties in detail using Ocular Response Analyzer (ORA) and Corvis ST (CST) tonometry and to analyze the association between corneal biomechanical properties and the frequency of intravitreal anti-vascular endothelial growth factor (VEGF) injections (FIV) in AS eyes with choroidal neovascularization (CNV). Twenty-eight eyes of 15 patients with AS were enrolled. Mean age of AS patients was 67.9 ± 9.8 years. ORA and CST measurements were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Another previous study reported that the maximum deformation amplitude measured by CST was associated with the size of β-zone parapapillary atrophy,16 which has been reported to be associated with the development, severity, progression, and location of glaucoma 1720. Our recent studies also suggested that CST parameters were associated with the activity and prognosis of angioid streaks,21 and also the severity22 and progression23 of glaucoma. However, a different study reported no relationship between ORA-measured corneal hysteresis (CH) and β-zone parapapillary atrophy 24.…”
Section: Introductionsupporting
confidence: 53%
“…Another previous study reported that the maximum deformation amplitude measured by CST was associated with the size of β-zone parapapillary atrophy,16 which has been reported to be associated with the development, severity, progression, and location of glaucoma 1720. Our recent studies also suggested that CST parameters were associated with the activity and prognosis of angioid streaks,21 and also the severity22 and progression23 of glaucoma. However, a different study reported no relationship between ORA-measured corneal hysteresis (CH) and β-zone parapapillary atrophy 24.…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, it can be of value in gene therapy studies among these systemic entities. Recently, an association between corneal biomechanical properties and the number of anti-VEGF injections in these eyes was highlighted, 145 but more studies are needed in order to address the potential usefulness of these properties in risk prediction.…”
Section: Corneal Biomechanics and Angioid Streaks/pseudoxanthoma Elasmentioning
confidence: 99%
“…Reduced energy dissipation in the cornea may cause higher vulnerability to these stresses 41 . Furthermore, we recently reported that angioid streaks were significantly associated with the corneal biomechanical properties as measured by using CST 48 . Considering these facts, the newly proposed Monot1-2 may also be useful in these diseases, and this should be further investigated in a future study.…”
Section: Discussionmentioning
confidence: 98%